Factors associated with midwives' job satisfaction and experience of work: a cross-sectional survey of midwives in a tertiary maternity hospital in Melbourne, Australia. Issue 2 (March 2022) - Matthews, Robyn; Hyde, Rebecca; Llewelyn, Fleur; Shafiei, Touran; Newton, Michelle; Forster, Della A.
Abstract: Background: Significant factors affecting the Australian maternity care context include an ageing, predominantly part-time midwifery workforce, increasingly medicalised maternity care, and women with more complex health/social needs. This results in challenges for the maternity care system. There is a lack of understanding of midwives' experiences and job satisfaction in this context. Aim: To explore factors affecting Australian midwives' job satisfaction and experience of work. Methods: In 2017 an online cross-sectional questionnaire was used to survey midwives employed in a tertiary hospital. Data collected included characteristics, work roles, hours, midwives' views and experiences of their job. The Midwifery Process Questionnaire was used to measure midwives' satisfaction in four domains: Professional Satisfaction, Professional Support, Client Interaction and Professional Development. Data were analysed as a whole, then univariate and multivariate logistic regression analyses conducted to explore any associations between each domain, participant characteristics and other relevant factors. Findings: The overall survey response rate was 73% (302/411), with 96% (255/266) of permanently employed midwives responding. About half (53%) had a negative attitude about their Professional Support and Client Interaction (49%), and 21% felt negatively about Professional Development. The majority felt positively regarding Professional Satisfaction (85%). The main factors that impacted midwives' satisfaction was inadequate acknowledgment from the organisation and needing more support to fulfil their current role. Conclusion: Focus on leadership and mentorship around appropriate acknowledgement and support may impact positively on midwives' satisfaction and experiences of work. A larger study could explore how widespread these findings are in the Australian maternity care setting.